Influence of DINESERV toward e-WOM, mediated by satisfaction and revisit intention at local coffee shop in South Jakarta - Felix Goenadhi; Silvia Dewi Novianti; Dhanik Puspitasari (President University, 2022)
Local coffee shop in Indonesia is growing, especially in Jakarta. In 2018, in Jakarta, there are predicted there will be 1.500 local coffee shops. They are rivalry among the coffee shop to satisfy their customer. Therefore, the tangible aspect is a must because, nowadays, people come to the coffee shop to hang out with their friends, and responsiveness because some of the coffee shops have a complaint from google reviews or E-WOM about the satisfaction. This research uses using a quantitative method to examine the influence of DINESERV on satisfaction at a local coffee shop in South Jakarta. The sample for this research is the customer who drinks coffee at a coffee shop in South Jakarta, and the sampling method uses purposive sampling with a minimum of 100 respondents. This questionnaire spread and got 314 respondents. This study reveals that E-WoM is influenced by tangibles, empathy, customer satisfaction, and revisit intentions. However, reliability, responsiveness, and assurance were found to be rejected. Discussion in this research for an entrepreneur that wants to make a coffee shop, to focus on the layout and ambiance of the coffee shop. The conclusion of this research is from 314 respondents who have visited a local coffee shop, dominate of a teenager, and in a week, they are visiting 1-2 times and buying behavior with a focus on local peers.